Role of tetraspanin CD9 molecule in fertilization of mammals - Jankovičová, J; Simon, Michal; Antalíková, Jana; Cupperová, Petra; Michalková, Katarína (Physiological research, 2015)
Fertilization process is a very clever and unique process comprising some essential steps resulting in formation of zygote. Tetraspanin CD9 is considered to be a serious candidate molecule participating in these events. The importance of CD9 has been discussed in relation to acrosome reaction, sperm-binding, sperm-penetration, sperm-egg fusion and eventually, egg activation. The abundant expression of CD9 oocyte plasma membrane and the presence of CD9-containing vesicles in the perivitelline space of intact oocytes have been confirmed. Despite the fact that majority of authors analyzed CD9 expressed on oocytes, several studies considered the function of sperm CD9, too. To understand CD9 involvement, various conditions of in vitro fertilization (IVF) assays using polyclonal as well as monoclonal antibodies or knockout mice were carried out. However, ambiguous data have been obtained about the importance of CD9 in sperm-egg binding or fusion. Although the current findings did not prove any hypothesis, the indispensable role of CD9 in fertilization process was not excluded and the precise role of CD9 remains unexplained.
Keywords: Fertilization; antigeny CD9; spermie; tetraspaniny; savci; Spermatozoa; Male; Tetraspanins; Animals; Tetraspanin 29; lidé; mužské pohlaví; oocyty; Mammals; Humans; zvířata; fertilizace; Oocytes